PENGELOLAAN ARSIP DI KANTOR DISTRIK WAIGEO BARAT KEPULAUAN KABUPATEN RAJA AMPAT PROVINSI PAPUA BARAT - Frety Matahelumual; Wiesje Ferdinandus (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Abstract Research with the title Archive Management at the West Waigeo District Office in Raja Ampat Regency was carried out to get an overview of optimizing employees in managing archives through: archival arrangement, archival storage, archival maintenance, re-discovery of archives to archive depreciation at the West Waigeo District Office in Raja Ampat Islands Province West Papua. This research was conducted using interview, observation and documentation research methods with qualitative research data processing involving 5 (five) informants taken as samples by means of Purposive Sampling. This study suggests that the process of managing records has not been carried out properly due to lack of human resources, equipment or equipment and a place for archival storage. It is necessary to optimize human resources (HR) specifically in the processing of records, awareness and discipline of employees, proposing the addition of equipment or facilities and infrastructure in archiving of records can be done well at the West Waigeo District office in Raja Ampat Islands.